2022
DOI: 10.1371/journal.pgph.0000386
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension screening, prevalence, treatment, and control at a large private hospital in Kampala, Uganda: A retrospective analysis

Abstract: Adult hypertension prevalence in Uganda is 27%, but only 8% are aware of their diagnosis, accordingly treatment and control levels are limited. The private sector provides at least half of care nationwide, but little is known about its effectiveness in hypertension control. We analyzed clinical data from 39 235 outpatient visits among 17 777 adult patients from July 2017 to August 2018 at Uganda’s largest private hospital. We calculated blood pressure screening rate at every visit, and hypertension prevalence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 2 However, our findings is not in agreement with a study done in Uganda which found a prevalence of hypertension of 27% and only 8% were aware of their diagnosis. 11 A national survey in Uganda found that only 7.7% of the people with hypertension were aware of their blood pressure status. 12 This difference might have been due to the differences in the study populations and the study design as our study was a cross sectional, but the study done by Majumdar and the team was retrospective, while the study by Gawattude and his team was a nationwide survey, while our study only investigated market salesperson.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, our findings is not in agreement with a study done in Uganda which found a prevalence of hypertension of 27% and only 8% were aware of their diagnosis. 11 A national survey in Uganda found that only 7.7% of the people with hypertension were aware of their blood pressure status. 12 This difference might have been due to the differences in the study populations and the study design as our study was a cross sectional, but the study done by Majumdar and the team was retrospective, while the study by Gawattude and his team was a nationwide survey, while our study only investigated market salesperson.…”
Section: Discussionmentioning
confidence: 99%
“…These baseline survey findings were pivotal in providing the key benchmarks to track NCD risk factors in the Ugandan population and informed the design of national-level NCD policy guidelines to address key NCD risk factors, including the importance of creating more public awareness about the NCDs and their risk factors [9,10]. Additional studies have described the barriers to hypertension prevention and management in rural settings, emphasized the need to increase the monitoring and screening of NCD risk factors at community levels through village health teams, and underscored broader access to essential NCD medicines, particularly in rural areas [11][12][13]. However, there have been a limited number of studies that examined the prevalence of hypertension and NCD risk factors together, along with factors associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Overall, 18.3% of patients achieved control. 3 Strategies are therefore needed to increase the prevention, detection, awareness, treatment, and control of hypertension in sub–Saharan Africa in general and in Uganda in particular. The WHO has set the following recommendations: to address population prevalence and control of hypertension through reducing modifiable risk factors, improving and expanding identification and treatment of people with hypertension, treatment intensification for patients whose BP is not controlled, ensuring access to medicines, tracking BP control rates in clinical settings, and measuring population prevalence.…”
Section: Introductionmentioning
confidence: 99%